Performance Assessment in STEM-EDP Project for High School Students: Validity Aspect - Roro Dinda Althaf Farah Zayyan Azizah; Nurul Fitriyah Sulaeman; Laili Komariyah (Kappa Journal, 2022)
Performance assessment is an assessment with written, action, and assignments that can provide better feedback on student performance and skills. The purpose of this research is to produce a valid performance assessment to be used in the assessment of STEM-EDP activity for global warming subjects. This research is an earlier stage of development research using the ADDIE development model with three stages, that is Analysis, Design, Development, while the implementation will be conduct as follow-up research. The performance assessment that has been developed is tested by expert judgement. The results of the validity test by two Physics Education lecturers at Mulawarman University and one teacher at SMA Negeri 5 Samarinda obtain that aspects of readability, aspects of suitability, aspects of construction, and aspects of product usability, each scored obtaining 88%, 82%, 85%, and 87% respectively that indicates that the four aspects are in the very good category. Based on these results, the STEM-EDP performance assessment of global warming subjects are suitable to use in implementation stage.